Navigating an Internship at a Residential Education and Medical Centre in Rural Kenya: Reflections of a Music Therapy Student - Luvai, Mufu (Voices: A World Forum for Music Therapy, 2023)
Little has been written from the perspective of a Kenyan student completing a music therapy internship at a mental rehabilitation institution in rural Kenya. At the time of writing this essay, music therapy was still not recognized as a profession in Kenya. This observation inspired me to fill a knowledge gap, encourage students to share their own experiences, and in the process, encourage aspiring music therapist students pioneering in other parts of Africa. I have divided my learnings into five themes based on my reflexive notes: (1) Mindset: Something out of nothing, (2) A staggered internship, (3) Transferring theory to practice, (4) Navigating workplace culture, and (5) Cultural sensitivity and musical multicultural competence. I advise the reader to take into consideration that these are my thoughts as a student undergoing a transformation. The essay not only describes my journey as an intern, but also provides me with a template for further reflections in my work as a music therapist. Compiling this essay has taught me that words on paper carry significant weight and have the ability to bring resolution to a problem or propagate it further. Through the internship, I came to learn that it is the role of music therapists to see beyond adversity; ignite hope where there is despair, and hold on to a future of possibilities.